2014
DOI: 10.4103/0970-2113.142118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of pulmonary hydatid cyst location on the surgical technique approaches

Abstract: Purpose:A hydatid cyst is the most common lung parasitic disease and is endemic in Iran. A hydatid cyst is more common in the right lung and lower lobes.Objective:The aim of this study was to assess surgical treatment of pulmonary hydatid cysts and whether the location of cyst affects surgical technique approaches.Materials and Methods:This study was performed on 87 patients with a pulmonary hydatid cyst who were referred to Qaem Hospital from 2010 to 2012. Selection of surgical technique was according to size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…We reported that the size, rupture of the cysts, the type of the surgery and abnormal ESR levels were significantly associated with increased postoperative complications. Similar to the results from Sadrizadeh, Haghi [ 3 ] study, the most common postoperative complication reported in our study was an air leak.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We reported that the size, rupture of the cysts, the type of the surgery and abnormal ESR levels were significantly associated with increased postoperative complications. Similar to the results from Sadrizadeh, Haghi [ 3 ] study, the most common postoperative complication reported in our study was an air leak.…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, through the portal vein and inferior vena cava, they reach the heart and the lungs, eventually. Lymphatic pathways, venal-venous anastomosis, and direct inhalation of the eggs are also the possible routes of the entrance of the eggs into the lungs [ 2 , 3 ]. Pulmonary hydatid cysts are diagnosed by means of imaging modalities, lab findings and patients’ history [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most common localization of hydatid cyst is the liver with 50–60% and secondly the lungs (10–30%) [ 11 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported left lower lobe predominance. [ 50 ] About 60% of cases occur in the lower lobes. Bilateral involvement occurs in 20% of cases, and multiple cysts in 30% of cases.…”
Section: Anatomical Locationmentioning
confidence: 99%
“…Ghosal et al . [ 50 ] reported single cyst and multiple cysts in 81.13% and 17.92% cases, respectively. Multiplicity depends on the number of the ova ingested and the number of embryos filtered via the liver and the lungs.…”
Section: Imaging Techniquesmentioning
confidence: 99%